Pimpinella anisum essential oil: A natural approach to amplifying fertility and reproductive well-being in the Saida Region - Ammam, Abdelkader; Belmamoun, Ahmed Reda; Zemour, Hafidh; Ammour, Fatima; Kaid, M’hamed; Villemin, Didier; Soufan, Walid; Belhouadjeb, Fathi Abdellatif (Future Science, 2023)
Infertility poses a significant challenge within the sheep population, hindering herd regeneration. Both rams and ewes are susceptible to infertility, prompting our objective of enhancing reproductive performance through the utilization of essential oils as a means to mitigate this issue. Essential oils have long been acknowledged for their medicinal properties and have been extensively employed in traditional medicine. Some essential oils have been reported to exert effects on male reproductive functions in both animals and humans.Pimpinella anisum, scientifically known as green anise, is a medicinal and aromatic annual plant renowned as one of the oldest medicinal herbs and widely used as a spice. In Algeria, essential oils extracted from Pimpinella anisum are consumed on a wide scale; however, their potential in enhancing ram fertility has remained unexplored.To improve the fertility of the Rembi breed sheep population, rams were randomly selected for this study. These rams underwent various experiments to evaluate their response to different concentrations (0, 0.5, and 1 mm/ram) of essential oil obtained from anise seeds using the hydro-distillation extraction method. Furthermore, the study encompassed an assessment of their key zootechnical characteristics over a one-year period.